2016
DOI: 10.1111/jfq.12251
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of Commercial Nixtamalized Maize (Zea mays L.) with Common Bean (Phaseolus vulgaris L.) Increased the Nutritional and Nutraceutical Content of Tortillas without Modifying Sensory Properties

Abstract: Common beans have been used to fortify maize tortillas increasing nutritional properties but affecting sensorial properties. The aim of this study was to evaluate the physicochemical and nutraceutical composition; and acceptability of tortillas formulated with maize and common bean. The physicochemical characterization showed no significant differences between common bean‐fortified (CBMF) and maize (CMF) tortillas regarding texture, rolability and puffing. Nutritionally, CBMF had higher protein (10.89%) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
10
0
4
Order By: Relevance
“…However, the above mentioned solvents are only suitable for the extraction of soluble phenolics. Bound phenolics need to be hydrolyzed with 2 mol/L NaOH and 12 mol/L HCl before further extraction (Aguilera et al., ; Ross, Beta, & Arntfield, ; Treviño‐Mejía, Luna‐Vital, Gaytán‐Martínez, Mendoza, & Loarca‐Piña, ). In addition, numerous studies have reported that the optimization of processing parameters plays a vital role in obtaining maximal polyphenols (Ghafoor, Choi, Jeon, & Jo, ; Jovanovic et al., ; Mourtzinos et al., ; Paleologou, Vasiliou, Grigorakis, & Makris, ; Wong, Li, Li, Razmovski‐Naumovski, & Chan, ; Zhang & Wang, ).…”
Section: Extraction Separation and Identification Methodsmentioning
confidence: 99%
“…However, the above mentioned solvents are only suitable for the extraction of soluble phenolics. Bound phenolics need to be hydrolyzed with 2 mol/L NaOH and 12 mol/L HCl before further extraction (Aguilera et al., ; Ross, Beta, & Arntfield, ; Treviño‐Mejía, Luna‐Vital, Gaytán‐Martínez, Mendoza, & Loarca‐Piña, ). In addition, numerous studies have reported that the optimization of processing parameters plays a vital role in obtaining maximal polyphenols (Ghafoor, Choi, Jeon, & Jo, ; Jovanovic et al., ; Mourtzinos et al., ; Paleologou, Vasiliou, Grigorakis, & Makris, ; Wong, Li, Li, Razmovski‐Naumovski, & Chan, ; Zhang & Wang, ).…”
Section: Extraction Separation and Identification Methodsmentioning
confidence: 99%
“…UU.). De las curvas fuerza-tiempo se determinaron los parámetros texturales de la siguiente manera: dureza (fuerza necesaria para alcanzar una deformación), cohesividad (fuerza de uniones internas que proporcionan el cuerpo a la muestra), adhesividad (trabajo necesario para superar las fuerzas atractivas entre la superficie del alimento y la superficie de otro), y resorteo (relación en la que un material deformado regresa a su condición original después de que la fuerza de deformación es removida), de acuerdo con lo reportado por Szczesniak (1963) y Bourne (1978). Para la prueba de penetración, 50 g de masa moldeada en forma de cilindro (5,0 cm de diámetro por 2,0 cm de altura, aproximadamente) fueron penetrados con una sonda esférica de 1,27 cm de diámetro, a una velocidad de 1 mm/s, hasta una profundidad de 18 mm, en el mismo texturómetro.…”
Section: Transformación Y Agroindustriaunclassified
“…Se llevó a cabo la prueba utilizando dos rebanadas de pan (15,0 ± 1,0 mm) cortadas del centro de la hogaza para ser comprimidas (40 %) en dos ciclos consecutivos con un periodo de reposo de 5 s a una velocidad de 1 mm/s, por medio de una sonda de acrílico de 40 mm de diámetro adaptada al mismo texturómetro. De las curvas fuerza-tiempo se determinó la dureza (fuerza necesaria para alcanzar una deformación), la cohesividad (fuerza de uniones internas que proporcionan el cuerpo a la muestra), el resorteo (relación en la que un material deformado regresa a su condición original después de que la fuerza de deformación es removida) y la masticabilidad (energía requerida para masticar el alimento para ser deglutido) (Bourne, 1978;Szczesniak, 1963). Todos los análisis se llevaron a cabo por quintuplicado para cada tratamiento.…”
Section: -719unclassified
“…Tortillas represent an excellent vehicle to enhance the nutritional status of tortillas consumers (Mexicans). Several researchers have reported improvements in maize tortilla quality with regard to nutritional and nutraceutical properties throughout the addition of several types of flours: Common bean (Treviño-Mejía et al, 2016), soybean (Chuck-Hernández and Serna-Saldívar, 2019), and sprouted soybean (Inyang et al, 2019). The fortification of creole blue maize tortillas with pseudocereals flours represents an alternative to improve their nutritional and nutraceutical properties.…”
Section: Introductionmentioning
confidence: 99%